Application of nanoscience and technology for increasing the shelf life of seeds and fruits of horticulture crops - Keerthi Priya, G; Kumanan, K; Shanmuganathan, M; Indu Rani, C; Vijayakumar, M; Ashokkumar, G (Plant Science Today, 2026)
The use of nanoscience and technology in horticulture has attracted significant attention due to its potential to enhance the shelf life of seeds and fruits. Nanotechnology-based methods, such as nanocoatings, nanoencapsulation, nanoemulsions and nano-packaging, have shown promising results in preserving the freshness of fruits and seeds by minimizing microbial contamination, reducing post-harvest losses and improving seed viability. Nanomaterials such as silver nanoparticles, titanium dioxide, zinc oxide, chitosan and carbon-based nanostructures exhibit antimicrobial, antioxidant and controlled-release properties, which contribute to extending the storage periods. This review examines the recent advancements in nanotechnology for post-harvest preservation, emphasizing the mechanisms, benefits and challenges associated with these innovative techniques. Biodegradable nanoparticles are emerging as environmentally friendly alternatives to chemical preservatives in food preservation. Additionally, advanced nano biosensors are being developed to measure freshness in real time and detect spoilage at an early stage. Research and policy development are necessary to address issues including cost-effectiveness, regulatory concerns and environmental impacts, despite these encouraging benefits. Furthermore, the environmental and safety concerns related to nanomaterial applications in horticultural products are discussed. Integrating nanotechnology in horticulture presents a sustainable and efficient solution to meet global food security demands by minimizing post-harvest losses and improving crop productivity and food security, making it a crucial area for future innovation and investment.